Raw pollen counts of MIS 31 from IODP Site 339-U1385, SW Iberian margin - Oliveira, Dulce; Sanchez Goñi, Maria Fernanda; Naughton, Filipa; Polanco-Martínez, Josué M; Jimenez-Espejo, Francisco J; Grimalt, Joan O; Martrat, Belén; Voelker, Antje H L; Trigo, Ricardo M; Hodell, David A; Abrantes, Fatima F; Desprat, Stéphanie (In: Oliveira, D et al. (2025): Deep-sea pollen record of MIS 31 from IODP Site 339-U1385, SW Iberian margin [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986770, 2025)
Raw counts of identified pollen and spores IODP Site 339-U1385, SW Iberian margin, for the early Pleistocene interval MIS 32-30 (1,100-1,050 ka)
Keywords: Iberian margin; Interglacial; Mediterranean vegetation; MIS 31; pollen analysis